The Relationship Between Exposure to Cigarette Smoke and the Incidence of Acute Respiratory Infections (ARI) in Toddlers - Elna Sari; Lina Darmayanti Bainuan; Paruhum Tiruon Ritonga (CV. Get Press Indonesia, 2025)
Background. Acute respiratory infections (ARI) are one of the most common health problems affecting children under five years of age (toddlers), especially in developing countries such as Indonesia. Exposure to cigarette smoke in the home environment is a significant environmental determinant of ARI in toddlers and is an important basis for prevention efforts through family education and smoke-free home policies. Methods. This study used a quantitative approach with a cross-sectional design. Data were collected through direct interviews with parents or guardians of toddlers using a prepared questionnaire and confirmation of acute respiratory infection (ISPA) cases through records of visits to health facilities in the last three months. Bivariate analysis was performed using the Chi-Square (2) test. Results. The results of univariate and bivariate analyses showed that the majority of the toddlers in the working area of the Muna District Community Health Centre in the Ambacang Puskesmas work area were exposed to smoke, which was as much as 60%, and more than half, which were 56%, had ARI. Furthermore, the results of bivARIate analysis showed that there was a statistically significant relationship between exposure to smoke and ARI (p = 0.003). Conclusion. The findings of this study provide a strong foundation for health professionals and policymakers to design educational programs and interventions that target reducing exposure to secondhand smoke for the health of children.